2010
DOI: 10.1002/dvdy.22406
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant EDA or Sonic Hedgehog rescue the branching defect in Ectodysplasin A pathway mutant salivary glands in vitro

Abstract: Hypohidrotic ectodermal dysplasia (HED) is characterized by defective ectodermal organ development. This includes the salivary glands (SGs), which have an important role in lubricating the oral cavity. In humans and mice, HED is caused by mutations in Ectodysplasin A (Eda) pathway genes. Various phenotypes of the mutant mouse Eda Ta/Ta , which lacks the ligand Eda, can be rescued by maternal injection or in vitro culture supplementation with recombinant EDA. However, the response of the SGs to this treatment h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…These data combined with the fact that the expression level of Shh positively correlated with Eda signaling activity in vivo, implicates Shh as a key mediator downstream of Eda in developing salivary glands. While our manuscript was under review, Wells et al (Wells et al, 2010) reported the rescue of an Edar-deficient SMG branching defect (which was similar to that seen in Eda-null embryos) produced by recombinant Shh protein, further confirming the importance of Shh downstream of Eda/Edar.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These data combined with the fact that the expression level of Shh positively correlated with Eda signaling activity in vivo, implicates Shh as a key mediator downstream of Eda in developing salivary glands. While our manuscript was under review, Wells et al (Wells et al, 2010) reported the rescue of an Edar-deficient SMG branching defect (which was similar to that seen in Eda-null embryos) produced by recombinant Shh protein, further confirming the importance of Shh downstream of Eda/Edar.…”
Section: Discussionsupporting
confidence: 68%
“…In line with this, qRT-PCR analysis of Eda-null SMGs at later stages (E16 to newborn) indicated that both Shh and Fgf8 were downregulated (Melnick et al, 2009). Wells et al (Wells et al, 2010) reported that treatment with Fgf8 protein did not rescue the branching defect of Edar mutant SMGs, but did increase bud surface area. It is likely that many signaling molecules, acting either in the same or in parallel pathways, function as proliferative cues to promote epithelial growth and branching of SMG (Patel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This ex ovo rescue study [50] implicated defective FGF signalling as underlying the failure of feather development in sc/sc , though such mutant rescue data should be interpreted cautiously in the absence of genetic evidence, since it is possible that such phenotypic rescues are achieved via a pathway independent or downstream of the primary causative genetic defect. For example, it has been shown that tooth and gland defects in Eda mutant mice can be rescued with recombinant Fgf10 and Shh, as well as by recombinant Eda itself [51,52]. …”
Section: Discussionmentioning
confidence: 99%
“…An air interface technique was used because full liquid submersion resulted in dissociation of overlying epidermis. The air interphase technique has been used successfully for other explants of tissue normally fully submerged in vivo (Wells et al, 2010; Bull et al, 2011). Others have shown that air interface can accelerate barrier development in rats (Komuves et al, 1999), however human tissue used in these studies is developmentally 8–12 weeks from this stage and it remains unknown whether air interface might have a similar effect on human scalp development.…”
Section: Methodsmentioning
confidence: 99%